The impact of modern technology on facilitating criminal procedures comparative study - Faraj, Sirwan Othman Faraj; Saleh, Asst.Prof.Dr. Rzgar Abulkarim Saleh (Sulaimani Journal for Humanities, 2025)
The scientific and technological developments, along with the digital revolution in the modern era and the occurrence of devices and artificial intelligence have led to fundamental changes in the rules of criminal procedure in contemporary legislation. New means have emerged to facilitate criminal proceedings, most notably video conferencing, which provides greater flexibility and reduces effort and time. With the increasing reliance on modern technology in criminal proceedings, a major challenge has emerged in achieving a balance between the principle of prompt justice and the principle of fair justice, given the conflict between these two principles. On the one hand, remote criminal proceedings aim to expedite litigation by facilitating procedures and reducing time, effort, and costs. On the other hand, the requirements of a fair trial require preserving its guarantees, such as oral pleadings, public trials, and the rights of parties to the lawsuit, such as personal presence at trial sessions. Undoubtedly, these are new legal challenges that pose a dilemma that requires further study to ensure compatibility between the use of these technologies and the requirements of a fair trial.